2014
DOI: 10.1371/journal.pone.0113333
|View full text |Cite
|
Sign up to set email alerts
|

MyD88 Deficiency Alters Expression of Antimicrobial Factors in Mouse Salivary Glands

Abstract: The surfaces of oral mucosa are protected from infections by antimicrobial proteins and natural immunoglobulins that are constantly secreted in saliva, serving as principal innate immune defense in the oral cavity. MyD88 is an important adaptor protein for signal transduction downstream of Toll-like receptors and TACI, receptors for regulation of innate immunity and B cell responses, respectively. Although MyD88-mediated signaling has a regulatory role in the intestinal mucosal immunity, its specific role in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Spleen B220 + cells were slightly increased in Myd88 -deficient mice (Fig. 2a ), but similar observations have been reported in other mouse strains 28 , 29 . T cell subsets in the spleen and SGALNs were almost identical in Myd88 +/+ and Myd88 −/− NOD mice (Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Spleen B220 + cells were slightly increased in Myd88 -deficient mice (Fig. 2a ), but similar observations have been reported in other mouse strains 28 , 29 . T cell subsets in the spleen and SGALNs were almost identical in Myd88 +/+ and Myd88 −/− NOD mice (Fig.…”
Section: Resultssupporting
confidence: 89%
“…NOD/ShiLtJ (NOD) mice were obtained from Charles River Laboratories, Japan (Yokohama, Japan). B6- Myd88 −/− mice were described previously 29 . A congenic strain, NOD.B6- Myd88 −/− , was generated by crossing NOD with B6- Myd88 −/− mice.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is interesting that bradykinin shows a similar proinflammatory effect in the exocrine system. Salivary glands are involved in the local immune reactions with their innate immunity-related receptors, including TLRs (39)(40)(41). Thus, further investigation of the bradykinin-mediated induction of salivary cytokines on the basis of our findings will eventually contribute to understanding the changes in salivary functions mediated by pathological conditions such as inflammation and angioedema.…”
Section: Discussionmentioning
confidence: 85%
“…IgA secretion by B‐1 cells was also investigated in extraperitoneal or pleural localizations, namely in lacrimal and salivary glands . Phenotypical analysis of mononuclear cells isolated from lacrimal glands showed that approximately 4% of cells were IgA + B cells, and IgA + B cells mainly belonged to the B‐1 lineage (B220 low ) as defined by CD5 surface expression .…”
Section: In Vivo Evidence For Iga Production By B‐1 Cellsmentioning
confidence: 99%
“…Another study addressed the impact of myeloid differentiation primary response gene 88 (MyD88) deficiency on mucosal immunity by analyzing salivary glands in Myd88 knockout mice . Both B‐1a and B‐1b cells were increased in the submandibular glands of Myd88 knockout compared to wild‐type mice, but no differences were detected in the number of B‐2 cells.…”
Section: In Vivo Evidence For Iga Production By B‐1 Cellsmentioning
confidence: 99%